Wax composition, wax for coating, and preparation method and application thereof

By using cobalt-based refined Fischer Wax, cobalt-based hydrogenated Fischer Wax, etc. to prepare the wax for coatings, the problem of insufficient performance of existing waxes for coatings is solved, and higher temperature resistance and lubrication performance are achieved, and internal and external lubrication of high-temperature precision instruments are suitable for high-temperature working precision instruments.

CN116200211BActive Publication Date: 2025-03-28CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111453708.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-01
Publication Date
2025-03-28
Estimated Expiration
2041-12-01

AI Technical Summary

Technical Problem

The existing waxes for coatings have poor water resistance, low friction resistance, poor surface strength, and are not resistant to high temperatures, which cannot meet the lubrication needs of high-temperature precision instruments.

Method used

Cobalt-based refined Fischer-Tropsch wax, cobalt-based hydrogenated Fischer-Tropsch wax, polymeric wax, microcrystalline wax and metal stearic acid salt are used to prepare the wax for coatings, and their performance is improved through specific mixing and processing steps.

Benefits of technology

The prepared coating wax has better temperature resistance, surface smoothness, wear resistance, bending resistance, dispersion and peel resistance, and can be used as an internal and external lubricant for high-temperature working precision instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003387097750000221
    Figure BDA0003387097750000221
Patent Text Reader

Abstract

The present invention relates to the technical field of wax for coatings, and specifically to a wax composition, wax for coatings, and a preparation method and application thereof. The present invention discloses a wax composition for coatings, the wax composition comprising: cobalt-based refined Fischer-Tropsch wax, cobalt-based hydrogenated Fischer-Tropsch wax, polymer wax, microcrystalline wax, and metal stearate; wherein the cobalt-based hydrogenated Fischer-Tropsch wax is a mixture of cobalt-based hydrogenated isomerized Fischer-Tropsch wax and cobalt-based hydrocracking Fischer-Tropsch wax. The coating wax prepared by using the wax composition of the present invention has good temperature resistance, surface smoothness, wear resistance, bending resistance, dispersibility and peeling resistance. The coating added with the coating wax has good wear resistance, peeling resistance and temperature resistance, and can also be used as an internal and external lubricant for tight instruments working at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wax for coatings, and in particular to a wax composition, wax for coatings, and a preparation method and application thereof. Background Art

[0002] Coating wax is mainly added to coatings in the form of additives. Wax additives generally exist in the form of water emulsions. They were originally used to improve the surface anti-expansion properties of the coating, mainly including improving the smoothness, scratch resistance and waterproofness of the coating. In addition, coating wax can also affect the rheological properties of the coating. Its addition can make the orientation of solid particles such as aluminum powder in metallic flash paint uniform. Therefore, coating wax is often added to various coatings, such as drug packaging coatings, anti-rust paints, varnishes, floor paints, etc. Among them, precision instruments working at high temperatures require internal and external lubricants. External lubricants can increase the lubricity of the plastic surface during processing, reduce the adhesion between the plastic and the metal surface, and reduce the mechanical shear force to a minimum, thereby achieving the purpose of the easiest processing and molding without damaging the performance of the plastic. Internal lubricants can reduce the internal friction of the polymer, increase the melting rate and melt deformation of the plastic, reduce the melt viscosity and improve the plasticization performance. The internal lubricant requires good compatibility with the polymer, reduces the friction between the molecular chains, and improves the flow performance; while the external lubricant requires a certain compatibility with the polymer to reduce the friction between the polymer and the surface of the processing machinery. Precision instruments require both external lubricants with a certain fluidity and internal lubricants that can reduce mechanical friction during mechanical operation. Currently, polyethylene wax is mainly used for coatings because it has moderate hardness. However, due to its poor water resistance, low anti-friction ability, poor surface strength, and uneven anti-peeling and high temperature resistance, domestic polyethylene wax cannot meet the requirements of coatings with high performance requirements when added alone, nor can it solve the problems of high temperature resistance, wear, and poor re-adhesion of coatings. In addition, precision instruments working at high temperatures usually require both internal and external lubricants, but the current external lubricants have poor adhesion, poor extrusion effect, and poor high temperature resistance of internal lubricants.

[0003] Fischer-Tropsch wax is a methylene polymer, an alkane synthesized from hydrocarbon-based syngas or natural gas, and is widely used in many fields: Fischer-Tropsch wax can be applied to plastic processing, such as injection molding, extrusion and granulation industries; Fischer-Tropsch wax is applied to the production process of masterbatches and modified plastics, which helps to disperse the filler and improve the smoothness during mixing; Fischer-Tropsch wax can be used as an external lubricant for PVC, its low viscosity can increase the production speed of the product, helps to disperse the filler during mixing, has a good effect in the extrusion of high-viscosity systems, and is 40-50% less than ordinary polyethylene wax, and can significantly improve the surface gloss of the product and have good re-adhesion; in dyes, melted Fischer-Tropsch wax can effectively wet the dye and reduce the basic viscosity; when Fischer-Tropsch wax is used in inks in the form of microparticles, it can improve the wear resistance and wrinkle resistance of the material; when applied to coatings, it can increase the glossiness and dispersibility of the coating and improve the gloss and smoothness of the product; when added to powder coating resins, it plays a lubricating role during the extrusion process, which can reduce the screw torque, reduce energy consumption and improve production efficiency. However, Fischer-Tropsch wax is usually used as a single-source additive, and when used in coatings, the high oil content of the Fischer-Tropsch wax causes the coating to peel off easily.

[0004] CN110305584A discloses a PE wax for hot-melt road marking paint, which is prepared by 95-type refined Fischer-Tropsch wax, zinc stearate, high molecular weight polyethylene wax, and PE oligomers. The coating PE wax has good dispersibility, adhesion, suitable construction open time, excellent surface leveling and system anti-settling effect, good anti-fouling and wetting properties. However, the present invention only improves the performance of hot-melt road performance paint wax, and does not solve the problems of poor waterproofness, low friction resistance, poor surface strength, and high temperature resistance of polyethylene wax, and cannot be applied to other fields. In addition, the present invention still does not solve the problem of poor adhesion and easy peeling of Fischer-Tropsch wax. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a wax composition, a wax for coating and a preparation method thereof, a coating and their applications. The coating wax has good toughness, good recyclability, neutral pH, good internal and external lubricity, good temperature resistance, surface smoothness, wear resistance, bending resistance, dispersibility and peeling resistance. The coating to which the coating wax is added has good wear resistance, peeling resistance and temperature resistance, and can also be used as an internal and external lubricant for tight instruments working at high temperatures.

[0006] The first aspect of the present invention provides a wax composition for coatings, wherein the wax composition comprises: cobalt-based refined Fischer-Tropsch wax, cobalt-based hydrogenated Fischer-Tropsch wax, polymer wax, microcrystalline wax, and metal stearate;

[0007] Wherein, the cobalt-based hydrogenated Fischer-Tropsch wax is a mixture of cobalt-based hydrogenated isomerized Fischer-Tropsch wax and cobalt-based hydrocracking Fischer-Tropsch wax.

[0008] A second aspect of the present invention provides a method for preparing a coating wax using the wax composition, comprising the following steps:

[0009] (1) mixing and melting the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax to obtain a liquid Fischer-Tropsch wax;

[0010] (2) performing a second mixing and melting of the liquid Fischer-Tropsch wax, a metal stearate and a dispersant to obtain a metal stearate Fischer-Tropsch wax mixture;

[0011] (3) performing a third mixing and melting of the metal stearate Fischer-Tropsch wax mixture, the polymer wax and the microcrystalline wax to obtain a liquid mixed wax;

[0012] (4) melting and mixing the liquid mixed wax and keeping it warm to obtain a liquid Fischer-Tropsch modified wax;

[0013] (5) granulating and screening the liquid Fischer-Tropsch modified wax to obtain coating wax;

[0014] Wherein, the auxiliary agent is added in step (3) and step (4) respectively or the auxiliary agent is added only in step (4).

[0015] The third aspect of the present invention provides a coating wax prepared by the above method.

[0016] A fourth aspect of the present invention provides a coating, wherein the coating contains the above-mentioned coating wax.

[0017] A fifth aspect of the present invention provides a use of the above-mentioned coating wax or the above-mentioned coating in precision instrument coatings.

[0018] The above technical solution is specifically embodied in:

[0019] 1. Compared with the traditional polyethylene wax powder, the coating wax of the present invention has better temperature resistance, surface smoothness, wear resistance, bending resistance, dispersibility and peeling resistance, good toughness, good recyclability, neutral pH, good internal and external lubricity, and different degrees of peeling resistance and temperature resistance can be controlled according to the ratio;

[0020] 2. The wax composition of the present invention contains cobalt-based refined Fischer-Tropsch wax and cobalt-based hydrogenated Fischer-Tropsch wax, which not only utilizes the high melting point and low viscosity characteristics of the cobalt-based refined Fischer-Tropsch wax to improve the temperature resistance, surface smoothness and wear resistance of the prepared coating wax, but the soft and sticky characteristics of the cobalt-based hydrogenated Fischer-Tropsch wax also improve the anti-re-stickiness of the prepared coating wax.

[0021] 3. The refined Fischer-Tropsch wax of the present invention is prepared by using Fischer-Tropsch wax prepared by cobalt-based fixed bed technology as raw material. The cobalt-based refined Fischer-Tropsch wax has a high drop melting point, and the aromatic content therein is less than 100 ppm by mass, and most of them are monocyclic aromatic hydrocarbons, which are non-toxic and environmentally friendly, and can be used as wax for food or drug packaging coatings.

[0022] 4. The wear resistance and temperature resistance of the coating to which the coating wax of the present invention is added are significantly improved, and the coating is suitable for high-temperature coatings. In addition, the coating to which the coating wax of the present invention is added has high-temperature viscosity, fluidity and friction resistance, and when used as a lubricant for high-temperature precision instruments, it can play a dual role as an internal lubricant and an external lubricant. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The first aspect of the present invention provides a wax composition for coatings, wherein the wax composition comprises: cobalt-based refined Fischer-Tropsch wax, cobalt-based hydrogenated Fischer-Tropsch wax, polymer wax, microcrystalline wax, and metal stearate;

[0025] Wherein, the cobalt-based hydrogenated Fischer-Tropsch wax is a mixture of cobalt-based hydrogenated isomerized Fischer-Tropsch wax and cobalt-based hydrocracking Fischer-Tropsch wax.

[0026] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the cobalt-based refined Fischer-Tropsch wax is 20-80 weight %, the amount of the cobalt-based hydrogenated Fischer-Tropsch wax is 5-30 weight %, the amount of the polymer wax is 0.5-30 weight %, the amount of the microcrystalline wax is 3-20 weight %, and the amount of the metal stearate is 1.5-20 weight %.

[0027] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the cobalt-based refined Fischer-Tropsch wax can be any one of 20 weight%, 25 weight%, 30 weight%, 35 weight%, 40 weight%, 45 weight%, 50 weight%, 55 weight%, 60 weight%, 65 weight%, 70 weight%, 75 weight%, 80 weight%, or a value within the range consisting of any two of the above values.

[0028] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the cobalt-based hydrogenated Fischer-Tropsch wax can be any one of 5 weight%, 10 weight%, 15 weight%, 20 weight%, 25 weight%, 30 weight%, or a value within the range consisting of any two of the above values.

[0029] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the polymer wax can be any one of 0.5 weight%, 1 weight%, 5 weight%, 6 weight%, 10 weight%, 15 weight%, 20 weight%, 25 weight%, 30 weight%, or a value within the range consisting of any two of the above values.

[0030] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the microcrystalline wax can be any one of 3 weight %, 5 weight %, 6 weight %, 10 weight %, 15 weight %, 20 weight % or a value within the range consisting of any two of the above values.

[0031] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the metal stearate can be any one of 1.5 weight%, 4 weight%, 5 weight%, 10 weight%, 15 weight%, 20 weight%, or a value within the range consisting of any two of the above values.

[0032] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the cobalt-based refined Fischer-Tropsch wax is 40-75% by weight, the amount of the cobalt-based hydrogenated Fischer-Tropsch wax is 10-20% by weight, the amount of the polymer wax is 6-25% by weight, the amount of the microcrystalline wax is 6-15% by weight, and the amount of the metal stearate is 3-20% by weight.

[0033] In some embodiments of the present invention, based on the total weight of the wax composition, the amount of the cobalt-based refined Fischer-Tropsch wax is 50-75 weight%, the amount of the cobalt-based hydrogenated Fischer-Tropsch wax is 5-20 weight%, the amount of the polymer wax is 5-15 weight%, the amount of the microcrystalline wax is 5-15 weight%, and the amount of the metal stearate is 1.5-10 weight%.

[0034] In some embodiments of the present invention, the average molecular weight of the polymer wax is 10,000-25,000 g / mol.

[0035] In some embodiments of the present invention, the polymer wax is at least one of polyethylene wax, polypropylene wax and polytetrafluoroethylene wax, and polyethylene wax is further preferred. Preferably, when the polymer wax is polypropylene wax, the prepared coating has high temperature resistance and chemical resistance, and the amount of the polypropylene wax is 1-5% by weight based on the total weight of the wax composition. Preferably, when the polymer wax is polytetrafluoroethylene wax, the prepared coating has good processing performance, and the amount of the polytetrafluoroethylene wax is 0.5-4% by weight based on the total weight of the wax composition.

[0036] The metal stearate in the present invention can be a metal stearate commonly used in the art. Preferably, the metal stearate in the present invention is selected from at least one of zinc stearate and calcium stearate.

[0037] The microcrystalline wax of the present invention may be a commonly used microcrystalline wax in the art, for example, it may be at least one of No. 70 microcrystalline wax and No. 80 microcrystalline wax.

[0038] In the present invention, the microcrystalline wax can be obtained by commercial purchase or by preparation. The microcrystalline wax is prepared by a method known to those skilled in the art, which will not be described in detail herein.

[0039] In the present invention, the "cobalt-based Fischer-Tropsch wax" refers to the Fischer-Tropsch wax prepared using cobalt-based fixed bed technology, the "cobalt-based refined Fischer-Tropsch wax" refers to the Fischer-Tropsch wax hydrogenated and refined using cobalt-based Fischer-Tropsch wax as raw material, and the "cobalt-based hydrogenated Fischer-Tropsch wax" refers to a mixture of cobalt-based hydrogenated isomerized Fischer-Tropsch wax and cobalt-based hydrocracking Fischer-Tropsch wax.

[0040] During the research process, the inventor unexpectedly discovered that cobalt-based refined Fischer-Tropsch wax has the characteristics of high melting point, low oil content and low aromatics content, and cobalt-based hydrogenated Fischer-Tropsch wax has the characteristics of low needle penetration and low shrinkage, which can improve the dispersibility of the prepared coating wax.

[0041] In some embodiments of the present invention, the cobalt-based refined Fischer-Tropsch wax has a drop melting point of 90-115°C, for example, 90°C, 95°C, 100°C, 105°C, or 115°C.

[0042] In some embodiments of the present invention, in order to further increase the high temperature adhesion of the prepared coating wax, the carbon number distribution of the cobalt-based refined Fischer-Tropsch wax is C 10 -C 140 .

[0043] In some embodiments of the present invention, the cobalt-based refined Fischer-Tropsch wax has an aromatic content of 30-100 ppm by weight, and the content of monocyclic aromatics in the aromatics accounts for 20-60% of the total weight of the aromatics.

[0044] In some embodiments of the present invention, based on the total weight of the cobalt-based refined Fischer-Tropsch wax, the n-alkane content of the cobalt-based refined Fischer-Tropsch wax is ≥ 95 wt %, wherein, based on the total weight of the cobalt-based refined Fischer-Tropsch wax, in the cobalt-based refined Fischer-Tropsch wax, C 10 -C 60 The normal alkane content is 24-37% by weight, C 61 -C 80 The content of normal alkanes is 32.5-41.5% by weight, C 81 The content of the above normal alkanes is 25-42.4% by weight.

[0045] In some embodiments of the present invention, the distillation range of the cobalt-based refined Fischer-Tropsch wax is 400-650°C, wherein the wax content at a distillation range of 550-650°C accounts for more than 45% by weight of the total weight of the cobalt-based refined Fischer-Tropsch wax, preferably 50-85% by weight. In some embodiments of the present invention, the wax at a distillation range of 500-650°C accounts for 70-100% by weight of the total weight of the cobalt-based refined Fischer-Tropsch wax. When the cobalt-based refined Fischer-Tropsch wax meets the above conditions, the obtained coating wax has good temperature resistance.

[0046] The carbon number distribution of cobalt-based refined Fischer-Tropsch wax is measured by chromatography; the content of normal alkanes is measured by gas chromatography; the content of normal alkanes with different carbon number distributions is measured by gas chromatography; the wax content in the distillation range and the distillation range of 500-650°C and 550-650°C is measured by high-temperature simulated distillation; the content of aromatics is measured by UV-visible spectroscopy; and the drop melting point is measured by the GB / T8026 standard method.

[0047] In some embodiments of the present invention, in order to further increase the adhesion at high temperature and reduce the shrinkage, the cobalt-based hydrogenated Fischer-Tropsch wax has a drop melting point of 70-100°C.

[0048] In some embodiments of the present invention, in order to further improve the anti-friction property of the prepared coating, the kinematic viscosity of the cobalt-based hydrogenated Fischer-Tropsch wax at 100° C. is 11-30 mm / s.

[0049] In some embodiments of the present invention, the carbon number distribution of the cobalt-based hydrogenated Fischer-Tropsch wax is C 10 -C 120 .

[0050] In some embodiments of the present invention, the cobalt-based hydrogenated Fischer-Tropsch wax has a needle penetration of 7-30 (0.1 mm) and an oil content of 0.01-5 wt%.

[0051] In some embodiments of the present invention, the average molecular weight of the cobalt-based hydrogenated Fischer-Tropsch wax is 1200-2500 g / mol. When the average molecular weight of the cobalt-based hydrogenated Fischer-Tropsch wax is within the above range, the wear resistance of the prepared coating wax can be improved.

[0052] In some preferred embodiments of the present invention, in order to further improve the wear resistance and temperature resistance of the prepared coating wax, the carbon number distribution of the cobalt-based hydrogenated Fischer-Tropsch wax is C 25 -C 120 .

[0053] In some embodiments of the present invention, in order to improve the ductility of the final coating, the content of the cobalt-based hydroisomerized wax is 5-15% by weight, and the content of the cobalt-based hydrocracking wax is 85-95% by weight, based on the total weight of the cobalt-based hydrogenated Fischer-Tropsch wax.

[0054] In some embodiments of the present invention, the shrinkage rate of the cobalt-based hydrogenated Fischer-Tropsch wax is 0.2-1.0%.

[0055] The average molecular weight of the cobalt-based hydrogenated Fischer-Tropsch wax is measured by gas chromatography; the carbon number distribution is measured by chromatography; the kinematic viscosity at 100°C is measured by a viscometer according to the GB / T265 standard method; the drop melting point is measured by the GB / T8026 standard method; the needle penetration is measured by the ASTM D-1321 standard method; the oil content is measured by the GB / T3554 standard method; and the shrinkage is measured by the DIN16901 standard method.

[0056] In some preferred embodiments of the present invention, the preparation method of the cobalt-based refined Fischer-Tropsch wax is as follows: at 230-340°C, under the feed condition of hydrogen-to-oil ratio of 500-2000, the pressure is controlled at 5.5-6.5 MPa, and the wax space velocity is 1-3 h -1 , in the presence of a noble metal catalyst, the cobalt-based Fischer-Tropsch wax is reacted to obtain the cobalt-based refined Fischer-Tropsch wax. The noble metal catalyst may be a noble metal catalyst commonly used in the art for preparing cobalt-based refined Fischer-Tropsch wax, for example, a Pt / Al2O3 catalyst. The cobalt-based refined Fischer-Tropsch wax prepared by the above preparation method has a low aromatic content.

[0057] In some embodiments of the present invention, the cobalt-based Fischer-Tropsch wax is a No. 95-120 cobalt-based Fischer-Tropsch wax.

[0058] In the present invention, the cobalt-based hydrogenated Fischer-Tropsch wax refers to a mixture of cobalt-based hydrogenated isomerized Fischer-Tropsch wax and cobalt-based hydrocracking Fischer-Tropsch wax.

[0059] In some preferred embodiments of the present invention, the cobalt-based hydrogenated Fischer-Tropsch wax is prepared by the following method: cobalt-based Fischer-Tropsch wax is reacted in the presence of hydrocracking and an isomerized composite catalyst to obtain the cobalt-based hydrogenated Fischer-Tropsch wax, wherein the reaction conditions are: temperature 260-360°C, hydrogen-to-oil ratio 500-2000, pressure 5-7MPa, and feed space velocity of the cobalt-based Fischer-Tropsch wax 1-2.5h -1 . Preferably, the cracking and isomerization composite catalyst refers to a mixed catalyst of a hydroisomerization catalyst and a hydrocracking catalyst, and the weight ratio of the hydroisomerization catalyst to the hydrocracking catalyst is 0.2-3:1. In some embodiments of the present invention, in order to further reduce the carbon number distribution range of the cobalt-based hydrogenated Fischer-Tropsch wax, increase the isomerization rate of the product wax (i.e., the content of the hydroisomerized wax), and thus improve the flexibility of the prepared coating wax, the cobalt-based Fischer-Tropsch wax is a No. 120 cobalt-based Fischer-Tropsch wax. Among them, the hydroisomerization catalyst and the hydrocracking catalyst can be conventionally selected in the art, for example, the hydrocracking catalyst can be a Pt / Si-Al catalyst (for example, it can be a FC-32 catalyst), and the hydroisomerization catalyst can be a Pt / molecular sieve catalyst (for example, it can be a SLD-821 catalyst).

[0060] In some embodiments of the present invention, in order to improve the performance of the coating wax or coating obtained, the wax composition may further include an auxiliary agent. Preferably, the auxiliary agent is at least one of beeswax, PE oligomer, pentaerythritol stearate (PETS), ethylene bis stearamide (EBS), an emulsifier and a rust inhibitor.

[0061] In some embodiments of the present invention, in order to increase the gloss of the prepared coating, the wax composition may further include beeswax, and the amount of the beeswax is 0.2-5% by weight based on the total weight of the wax composition.

[0062] In some embodiments of the present invention, in order to reduce the acid value of the prepared coating, the wax composition may further include PE oligomers, and the amount of the PE oligomers is 1-10 wt %, preferably 3-8 wt %, based on the total weight of the wax composition.

[0063] The PE oligomer in the present invention is a low molecular weight polyethylene wax. In some embodiments of the present invention, the average molecular weight of the PE oligomer is 7000-9000 g / mol.

[0064] In some embodiments of the present invention, in order to further improve the chemical stability of the prepared coating, the mass ratio of the polymer wax to the PE oligomer is 0.2-2:1.

[0065] In some embodiments of the present invention, in order to improve the lubricity of the coating, the coating wax may further include pentaerythritol stearate (PETS), and the amount of the pentaerythritol stearate (PETS) is 3-15% by weight, preferably 5-10% by weight, based on the total weight of the coating wax.

[0066] In some embodiments of the present invention, in order to increase the compatibility of various waxes, the coating wax may further include ethylene bisstearamide (EBS), and the amount of ethylene bisstearamide (EBS) is 2-20% by weight, preferably 5-10% by weight, based on the total weight of the coating wax.

[0067] When the wax composition contains the above-mentioned contents of PETS and EBS at the same time, PETS and EBS have a synergistic effect, which can further improve the internal and external wear resistance.

[0068] In some embodiments of the present invention, in order to improve the rust-proof performance of the prepared coating wax, the wax composition may further include a rust-proof agent, and the amount of the rust-proof agent is 0.5-5% by weight, preferably 0.8-3% by weight, based on the total weight of the wax composition. The rust-proof agent of the present invention may be a rust-proof agent commonly used in the art, for example, at least one of triethanolamine, benzotriazole, and pentaerythritol monooleate.

[0069] In some embodiments of the present invention, the wax composition may further include an emulsifier. Preferably, the amount of the emulsifier is 1-5% by weight based on the total weight of the wax composition.

[0070] In some embodiments of the present invention, the wax composition may further include a dispersant. Preferably, the amount of the dispersant is 0.1-2% by weight based on the total weight of the wax composition.

[0071] In the present invention, the sum of the contents of all components in the wax composition is 100 wt%. In the present invention, the dispersant may be a commonly used dispersant in the art, for example, the dispersant of Guangzhou Houhuan Chemical Additive Co., Ltd. Wax dispersion and / or styrene acrylic resin.

[0072] The emulsifier described in the present invention can be an emulsifier commonly used in the art.

[0073] A second aspect of the present invention provides a method for preparing a coating wax using the wax composition, comprising the following steps:

[0074] (1) mixing and melting the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax to obtain a liquid Fischer-Tropsch wax;

[0075] (2) performing a second mixing and melting of the liquid Fischer-Tropsch wax, a metal stearate and a dispersant to obtain a metal stearate Fischer-Tropsch wax mixture;

[0076] (3) performing a third mixing and melting of the metal stearate Fischer-Tropsch wax mixture, the polymer wax and the microcrystalline wax to obtain a liquid mixed wax;

[0077] (4) melting and mixing the liquid mixed wax and keeping it warm to obtain a liquid Fischer-Tropsch modified wax;

[0078] (5) granulating and screening the liquid Fischer-Tropsch modified wax to obtain coating wax;

[0079] Wherein, the auxiliary agent is added in step (3) and step (4) respectively or the auxiliary agent is added only in step (4).

[0080] In some embodiments of the present invention, each step is carried out with stirring. Preferably, in step (1), the temperature of the first mixed melting is 120-180°C, and the stirring speed of the first mixed melting is 10-50r / min; in step (2), the temperature of the second mixed melting is 140-180°C, and the stirring speed is 10-50r / min; in step (3), the temperature of the third mixed melting is 140-180°C, and the stirring speed of the third mixture melting is 10-50r / min; in step (4), the melting temperature is 120-140°C, the insulation temperature is 150-175°C, the stirring speed during insulation is 10-50r / min, and the insulation time is 1-6h.

[0081] In some embodiments of the present invention, the granulation in step (5) can be performed by conventional techniques in the art. Preferably, the granulation of the present invention is performed by a granulation tower, the tower wall of the granulation tower is preferably a stainless steel tower wall, and the granulation nozzle of the granulation tower is preferably a stainless steel mesh nozzle.

[0082] In some embodiments of the present invention, the screening in step (5) is through a 80-100 mesh sieve.

[0083] In the present invention, the amounts and requirements of the components used in the preparation method are the same as those of the wax composition for coating in the present invention, and will not be described again to avoid unnecessary repetition.

[0084] The third aspect of the present invention provides a coating wax prepared by the above method.

[0085] In some embodiments of the present invention, the coating wax has a viscosity of less than 20 mm / s at 100° C., an ash content of less than 0.05% by weight, an oil content of less than 1.3% by weight, and a shrinkage of less than 1%.

[0086] In some embodiments of the present invention, the coating wax has a viscosity of less than 15 mm / s at 100° C., an ash content of less than 0.02% by weight, an oil content of less than 0.8% by weight, and a shrinkage of less than 1%.

[0087] In some preferred embodiments of the present invention, the coating wax has an oil content of 0.6-1.2% by weight, a shrinkage of 0.1-0.8%, and an ash content of 0.002-0.005% by weight.

[0088] In the present invention, the shrinkage rate of the coating wax is low, and the prepared coating has good temperature resistance.

[0089] In the present invention, the viscosity of the coating wax at 100°C is measured by the GB / T 9269-1988 standard method; the oil content of the coating wax is measured by the GB / T3554 standard method; the shrinkage is measured by the DIN16901 standard method; and the ash content is measured by the GB / T 1979-1979 standard method.

[0090] A fourth aspect of the present invention provides a coating, wherein the coating contains the above-mentioned coating wax.

[0091] In the present invention, the coating has strong abrasion resistance, corrosion resistance, adhesion, shrinkage and peeling resistance.

[0092] The coating wax of the present invention can be applied to common coatings in the art, preferably coatings that need to add coating wax with better temperature resistance, surface smoothness, wear resistance, and bending resistance, such as anti-rust paint, floor paint, and moisture-proof paint. The coating wax of the present invention is particularly suitable for being added to lubricants of precision instruments. Its anti-friction, fluidity, and strong mixed viscosity make it possible to be used as both an internal lubricant and an external lubricant, which can improve the fluidity of the coating and reduce the shrinkage rate during the molding of the coating, thereby improving the utilization efficiency of the coating and reducing the amount of coating used, and the final product obtains extremely high surface finish, smoothness, and anti-flaking properties.

[0093] In some preferred embodiments of the present invention, the coating is an internal lubricant and / or an external lubricant for precision instruments operating at high temperatures.

[0094] A fifth aspect of the present invention provides a use of the above-mentioned coating wax or the above-mentioned coating in precision instrument coatings.

[0095] In some embodiments of the present invention, the precision instrument coating is a precision instrument coating that works at high temperatures.

[0096] In some embodiments of the present invention, the precision instrument coating is a precision instrument lubricant, preferably an internal lubricant and / or an external lubricant.

[0097] In some preferred embodiments of the present invention, the precision instrument coating refers to an internal lubricant and / or an external lubricant for precision instruments operating at high temperatures.

[0098] The present invention will be described in detail below through examples. In the following examples, the abrasion of the coating wax is measured by the standard method of GB / T 1768-2006.

[0099] The glossiness of coating wax is measured by GB1743-89 standard method.

[0100] The hardness of coating wax is measured by BS EN ISO 11127-4-2011 standard method.

[0101] The impact strength of coating wax is measured by ISO 6272:1993(E) standard method.

[0102] The adhesion of coating wax is measured by GB5210-85 standard method.

[0103] The viscosity of the coating wax at 100°C is measured by the GB / T 9269-1988 standard method.

[0104] The oil content of coating wax is measured by GB / T3554 standard method.

[0105] The shrinkage of coating wax is measured by DIN16901 standard method.

[0106] The drop melting point of coating wax is measured by GB / T8026 standard method.

[0107] The ash content of coating wax is measured by the GB / T 1979-1979 standard method.

[0108] Unless otherwise specified, all raw materials used in the following examples were commercially available.

[0109] The carbon number distribution of cobalt-based refined Fischer-Tropsch wax is measured by chromatography; the content of normal alkanes is measured by gas chromatography; the content of normal alkanes with different carbon number distributions is measured by gas chromatography; the wax content in the distillation range and the distillation range of 500-650°C and 550-650°C is measured by high-temperature simulated distillation; the content of aromatics is measured by UV-visible spectroscopy; and the drop melting point is measured by the GB / T8026 standard method.

[0110] The average molecular weight of the cobalt-based hydrogenated Fischer-Tropsch wax is measured by gas chromatography; the carbon number distribution is measured by chromatography; the kinematic viscosity at 100°C is measured by a viscometer according to the GB / T265 standard method; the drop melting point is measured by the GB / T8026 standard method; the needle penetration is measured by the ASTM D-1321 standard method; the oil content is measured by the GB / T3554 standard method; and the shrinkage is measured by the DIN16901 standard method.

[0111] No. 90, No. 100 and No. 105 cobalt-based Fischer-Tropsch waxes were purchased from Shell and Sasol, with the brands being H1, H5 and SX105, respectively.

[0112] The preparation method of No. 120 cobalt-based Fischer-Tropsch wax is as follows: at a H2 / CO ratio of 2.05, a pressure of 2.5 MPa, a reaction temperature of 215°C, and a gas space velocity of 2500 h -1 Under the conditions of , in a fixed bed reactor, in the presence of a Co / TiO2 catalyst (the Co loading is 15 wt % based on the total weight of the catalyst), a No. 120 cobalt-based Fischer-Tropsch wax is obtained by reaction.

[0113] Polyethylene wax was purchased from Nanjing Tianshi with a brand name of PEW-0300 and an average molecular weight of 15000 g / mol.

[0114] In the following examples, the cracking and isomerization composite catalyst is a mixed catalyst of SLD-821 catalyst (hydroisomerization catalyst) and FC-32 catalyst (hydrocracking catalyst). Among them, SLD-821 catalyst was purchased from Shell Company; FC-32 catalyst was purchased from Fushun Petrochemical Research Institute of Sinopec Corporation.

[0115] The hydrotreating catalyst was FH-40 catalyst purchased from Fushun Petrochemical Research Institute of Sinopec.

[0116] The wax powder dispersant was purchased from Guangzhou Houhuan Chemical Additive Co., Ltd.

[0117] Example 1

[0118] (1) heating a beaker to 160° C., adding 60 parts by weight of cobalt-based refined Fischer-Tropsch wax and 10 parts by weight of cobalt-based hydrogenated Fischer-Tropsch wax, and stirring at a stirring speed of 20 r / min until the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax are melted to obtain liquid Fischer-Tropsch wax;

[0119] (2) Add 1.5 parts by weight of zinc stearate and 0.5 parts by weight of The wax powder dispersant is cooled and stirred at 150°C and a stirring speed of 20 r / min until the zinc stearate and The wax powder dispersant is melted to obtain a zinc stearate Fischer-Tropsch wax mixture;

[0120] (3) adding 15 parts by weight of polyethylene wax and 10 parts by weight of No. 70 microcrystalline wax, heating to 160° C., stirring at a stirring speed of 10 r / min until the polyethylene wax and the microcrystalline wax melt to obtain a liquid mixed wax;

[0121] (4) adding 3 parts by weight of triethanolamine, completely melting at 120° C., and then stirring at 160° C. and a stirring speed of 20 r / min for 4 h to obtain a liquid Fischer-Tropsch modified wax;

[0122] (5) The liquid Fischer-Tropsch modified wax obtained in step (4) is granulated by a stainless steel mesh nozzle, and then sieved through an 80-mesh sieve to obtain the coating wax.

[0123] The preparation method of cobalt-based refined Fischer-Tropsch wax is as follows: No. 100 cobalt-based Fischer-Tropsch wax is heated at 270°C, the pressure is controlled to be 6.2 MPa, and the wax oil air velocity is 1.2 h -1 , under the feed condition of hydrogen-to-oil ratio of 500, cobalt-based refined Fischer-Tropsch wax was obtained by FH-40 catalyst. The components of the obtained cobalt-based refined Fischer-Tropsch wax are carbon distribution number C 40 -C 120 The alkane, based on the total weight of the cobalt-based refined Fischer-Tropsch wax, has a normal alkane content of 95% by weight, wherein the cobalt-based refined Fischer-Tropsch wax C 10 -C 60 The normal alkane content is 32% by weight, C 61 -C 80 The normal alkane content is 35% by weight, C 81 The above normal alkanes account for 28% by weight. The distillation range of the cobalt-based refined Fischer-Tropsch wax is 450-650°C, the wax content in the distillation range of 500-650°C accounts for 70% of the total weight of the cobalt-based refined Fischer-Tropsch wax, and the wax content in the distillation range of 550-650°C accounts for 60% of the total weight of the cobalt-based refined Fischer-Tropsch wax. The drop melting point of the cobalt-based refined Fischer-Tropsch wax is 100.4°C, and the content of aromatics is 40ppm by weight.

[0124] The preparation method of cobalt-based hydrogenated Fischer-Tropsch wax is as follows: No. 90 cobalt-based Fischer-Tropsch wax is heated at 290°C, 6.5MPa, 500 hydrogen-to-oil ratio, and a feed space velocity of 1h -1 The cobalt-based hydrogenated Fischer-Tropsch wax was obtained by reacting with a cracking and isomerization composite catalyst (the weight ratio of the SLD-821 catalyst and the FC-32 catalyst was 1:1) under the reaction conditions of . The properties of the cobalt-based hydrogenated Fischer-Tropsch wax are shown in Table 1.

[0125] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0126] The coating with added wax has good surface smoothness, wear resistance and surface dispersion, good impact resistance, good internal and external lubricity, and good re-adhesion.

[0127] Example 2

[0128] (1) The beaker is heated to 150° C., 50 parts by weight of cobalt-based refined Fischer-Tropsch wax and 20 parts by weight of cobalt-based hydrogenated Fischer-Tropsch wax are added, and the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax are stirred at a stirring speed of 15 r / min until the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax are melted to obtain liquid Fischer-Tropsch wax;

[0129] (2) adding 5 parts by weight of calcium stearate and heating the mixture, stirring at 160° C. and a stirring speed of 15 r / min until the calcium stearate is melted to obtain a calcium stearate Fischer-Tropsch wax mixture;

[0130] (3) adding 10 parts by weight of polyethylene wax and 10 parts by weight of No. 80 microcrystalline wax, stirring at 160° C. and a stirring speed of 10 r / min until the polyethylene wax and the microcrystalline wax are melted to obtain a liquid mixed wax;

[0131] (4) adding 5 parts by weight of triethanolamine, completely melting at 140° C., and then stirring at 160° C. and a stirring speed of 20 r / min for 4 h to obtain a liquid Fischer-Tropsch modified wax;

[0132] (5) The liquid Fischer-Tropsch modified wax obtained in step (4) is granulated by passing it through a stainless steel mesh nozzle, and then sieved through an 80-mesh sieve to obtain the coating wax.

[0133] The preparation method of cobalt-based refined Fischer-Tropsch wax is as follows: No. 105 cobalt-based Fischer-Tropsch wax is heated at 280°C, under the feed condition of hydrogen-to-oil ratio of 500, the pressure is controlled to be 6.0 MPa, the wax-to-oil space velocity is 1.2 h -1 , a cobalt-based refined Fischer-Tropsch wax is obtained by using FH-40 catalyst. The cobalt-based refined Fischer-Tropsch wax component is a carbon distribution number in C 40 -C 100 The alkane, based on the total weight of the cobalt-based refined Fischer-Tropsch wax, has a normal alkane content of 98.5% by weight, wherein the cobalt-based refined Fischer-Tropsch wax C 10 -C 60 The normal alkane content is 25% by weight, C 61 -C 80 The normal alkane content is 41.5% by weight, C 81 The above normal alkanes account for 32% by weight. The distillation range of the cobalt-based refined Fischer-Tropsch wax is 500-650°C, and the wax content in the distillation range of 550-650°C accounts for 80% of the total weight of the cobalt-based refined Fischer-Tropsch wax. The drop melting point of the cobalt-based refined Fischer-Tropsch wax is 105°C, and the aromatic content is 45 ppm by weight.

[0134] The preparation method of cobalt-based hydrogenated Fischer-Tropsch wax is as follows: No. 105 cobalt-based Fischer-Tropsch wax is heated at 300°C, 6.5MPa, 500 hydrogen-to-oil ratio, and a feed space velocity of 1h -1 The cobalt-based hydrogenated Fischer-Tropsch wax was obtained by using a cracking and isomerization composite catalyst (the weight ratio of the SLD-821 catalyst and the FC-32 catalyst was 1.5:1) under the reaction conditions. The properties of the cobalt-based hydrogenated Fischer-Tropsch wax are shown in Table 1.

[0135] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0136] The coating with added wax has good surface smoothness, wear resistance and surface dispersion, and is impact-resistant.

[0137] Example 3

[0138] (1) heating a beaker to 160° C., adding 55 parts by weight of cobalt-based refined Fischer-Tropsch wax and 20 parts by weight of cobalt-based hydrogenated Fischer-Tropsch wax, and stirring at a stirring speed of 20 r / min until the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax are melted to obtain liquid Fischer-Tropsch wax;

[0139] (2) adding 5 parts by weight of zinc stearate to cool the mixture, stirring at 150° C. and at a stirring speed of 20 r / min until the zinc stearate is melted to obtain a zinc stearate Fischer-Tropsch wax mixture;

[0140] (3) adding 10 parts by weight of polyethylene wax and 10 parts by weight of No. 70 microcrystalline wax, heating to 160° C., stirring at a stirring speed of 10 r / min until the polyethylene wax and the microcrystalline wax melt to obtain a liquid mixed wax;

[0141] (4) After the liquid mixed wax is completely melted at 120° C., the mixture is stirred at 160° C. and a stirring speed of 20 r / min for 4 h to obtain a liquid Fischer-Tropsch modified wax;

[0142] (5) The liquid Fischer-Tropsch modified wax obtained in step (4) is granulated by a stainless steel mesh nozzle, and then sieved through an 80-mesh sieve to obtain the coating wax.

[0143] The preparation method of cobalt-based refined Fischer-Tropsch wax is as follows: No. 90 cobalt-based Fischer-Tropsch wax is heated at 270°C, under the feed condition of hydrogen-to-oil ratio of 500, the pressure is controlled to be 6.2 MPa, the wax-to-oil space velocity is 1.2 h -1 , through FH-40 catalyst, a cobalt-based refined Fischer-Tropsch wax is obtained. The components of the obtained cobalt-based refined Fischer-Tropsch wax are carbon distribution numbers in C 10 -C 80 The alkane content of the cobalt-based refined Fischer-Tropsch wax is 97% by weight, based on the total weight of the cobalt-based refined Fischer-Tropsch wax. 10 -C60 The normal alkane content is 37% by weight, C 61 -C 80 The normal alkane content is 35% by weight, C 81 The above normal alkane content accounts for 25% by weight. The distillation range of the cobalt-based refined Fischer-Tropsch wax is 400-650°C, the wax content in the distillation range of 500-650°C accounts for 70% of the total weight of the cobalt-based refined Fischer-Tropsch wax, and the wax content in the distillation range of 550-650°C accounts for 50% of the total weight of the cobalt-based refined Fischer-Tropsch wax. The drop melting point of the cobalt-based refined Fischer-Tropsch wax is 90.8°C, and the aromatic content is 32ppm by weight.

[0144] The preparation method of cobalt-based hydrogenated Fischer-Tropsch wax is as follows: No. 120 cobalt-based Fischer-Tropsch wax is heated at 320°C, 6.5MPa, 500 hydrogen-to-oil ratio, and a feed space velocity of 1h -1 The cobalt-based hydrogenated Fischer-Tropsch wax was obtained by reacting with a cracking and isomerization composite catalyst (the weight ratio of SLD-821 and FC-32 catalyst was 1:2) under the reaction conditions. The properties of the cobalt-based hydrogenated Fischer-Tropsch wax are shown in Table 1.

[0145] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0146] Example 4

[0147] (1) The beaker is heated to 150° C., 75 parts by weight of cobalt-based refined Fischer-Tropsch wax and 5 parts by weight of cobalt-based hydrogenated Fischer-Tropsch wax are added, and the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax are stirred at a stirring speed of 15 r / min until the cobalt-based refined Fischer-Tropsch wax and the cobalt-based hydrogenated Fischer-Tropsch wax are melted to obtain liquid Fischer-Tropsch wax;

[0148] (2) adding 5 parts by weight of zinc stearate and heating the mixture, stirring at 160° C. and a stirring speed of 15 r / min until the zinc stearate is melted to obtain a zinc stearate Fischer-Tropsch wax mixture;

[0149] (3) adding 10 parts by weight of polyethylene wax and 5 parts by weight of No. 80 microcrystalline wax, stirring at 160° C. and a stirring speed of 10 r / min until the polyethylene wax and the microcrystalline wax are melted to obtain a liquid mixed wax;

[0150] (4) After the liquid mixed wax is completely melted at 140° C., the mixture is stirred at 160° C. and a stirring speed of 20 r / min for 4 h to obtain a liquid Fischer-Tropsch modified wax;

[0151] (5) The liquid Fischer-Tropsch modified wax obtained in step (4) is granulated by passing it through a stainless steel mesh nozzle, and then sieved through an 80-mesh sieve to obtain the coating wax.

[0152] The preparation method of cobalt-based refined Fischer-Tropsch wax is as follows: No. 100 cobalt-based Fischer-Tropsch wax is heated at 280°C, under the feed condition of hydrogen-to-oil ratio of 500, the pressure is controlled to be 6.5 MPa, the wax-to-oil space velocity is 1.0 h -1 , a cobalt-based refined Fischer-Tropsch wax is obtained by using FH-40 catalyst. The cobalt-based refined Fischer-Tropsch wax component is a carbon distribution number in C 40- C 100 The alkane content is 98.8% by weight based on the total weight of the cobalt-based refined Fischer-Tropsch wax, wherein the cobalt-based refined Fischer-Tropsch wax C 10 -C 60 The normal alkane content is 31% by weight, C 61 -C 80 The normal alkane content is 40% by weight, C 81 The above normal alkane content is 27.8% by weight. The distillation range of the cobalt-based refined Fischer-Tropsch wax is 480-650°C, the wax content in the distillation range of 500-650°C accounts for 80% of the total weight of the cobalt-based refined Fischer-Tropsch wax, and the wax content in the distillation range of 550-650°C accounts for 72% of the total weight of the cobalt-based refined Fischer-Tropsch wax. The drop melting point of the cobalt-based refined Fischer-Tropsch wax is 100.2°C, and the aromatic content is 45ppm by weight.

[0153] The preparation method of cobalt-based hydrogenated Fischer-Tropsch wax is as follows: No. 110 cobalt-based Fischer-Tropsch wax is heated at 320°C, 6.5MPa, 600 hydrogen-to-oil ratio, and a feed space velocity of 1h -1 The cobalt-based hydrogenated Fischer-Tropsch wax was obtained by reacting with a cracking and isomerization composite catalyst (the weight ratio of SLD-821 and FC-32 catalyst was 1:1.6) under the reaction conditions. The properties of the cobalt-based hydrogenated Fischer-Tropsch wax are shown in Table 1.

[0154] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0155] Example 5

[0156] The coating wax was prepared according to the method of Example 4, except that:

[0157] The amount of cobalt-based refined Fischer-Tropsch wax is 70 parts by weight, the amount of cobalt-based hydrogenated Fischer-Tropsch wax is 5 parts by weight, the amount of zinc stearate is 10 parts by weight, the amount of polyethylene wax is 5 parts by weight, and the amount of No. 80 microcrystalline wax is 10 parts by weight.

[0158] The preparation method of the cobalt-based refined Fischer-Tropsch wax is as follows: No. 100 cobalt-based Fischer-Tropsch wax is heated at 260°C, 6MPa, and a wax oil air velocity of 1.3h -1 , under the feed condition of hydrogen-to-oil ratio of 500, a cobalt-based refined Fischer-Tropsch wax was obtained by using FH-40 catalyst. The cobalt-based refined Fischer-Tropsch wax component has a carbon distribution number of C 40- C 100The alkane, based on the total weight of the cobalt-based refined Fischer-Tropsch wax, has a normal alkane content of 98.2% by weight, wherein the cobalt-based refined Fischer-Tropsch wax C 10 -C 60 The normal alkane content is 32% by weight, C 61 -C 80 The normal alkane content is 39% by weight, C 81 The above normal alkane content accounts for 27.2% by weight. The distillation range of the cobalt-based refined Fischer-Tropsch wax is 480-650°C, the wax content in the distillation range of 500-650°C accounts for 84% of the total weight of the cobalt-based refined Fischer-Tropsch wax, and the wax content in the distillation range of 550-650°C accounts for 72% of the total weight of the cobalt-based refined Fischer-Tropsch wax. The drop melting point of the cobalt-based refined Fischer-Tropsch wax is 100.5°C, and the aromatic content is 45ppm by weight.

[0159] The preparation method of cobalt-based hydrogenated Fischer-Tropsch wax is as follows: No. 120 cobalt-based Fischer-Tropsch wax is heated at 330°C, 6.8MPa, 500 hydrogen-to-oil ratio, and a feed space velocity of 1.2h -1 The hydrogenated Fischer-Tropsch wax was obtained by reacting with a cracking and isomerization composite catalyst (the weight ratio of SLD-821 and FC-32 catalyst was 1:1) under the reaction conditions of . The properties of the cobalt-based hydrogenated Fischer-Tropsch wax are shown in Table 1.

[0160] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0161] Example 6

[0162] The coating wax was prepared according to the method of Example 4, except that:

[0163] The amount of cobalt-based refined Fischer-Tropsch wax is 50 parts by weight, the amount of cobalt-based hydrogenated Fischer-Tropsch wax is 20 parts by weight, the amount of zinc stearate is 4 parts by weight, the amount of polyethylene wax is 10 parts by weight, and the amount of No. 80 microcrystalline wax is 16 parts by weight.

[0164] The preparation method of the cobalt-based refined Fischer-Tropsch wax is as follows: No. 115 cobalt-based Fischer-Tropsch wax is heated at 230°C, 6.5 MPa, and a wax oil air velocity of 1.5 h -1 , under the feed condition of hydrogen-to-oil ratio of 600, a cobalt-based refined Fischer-Tropsch wax was obtained by using FH-40 catalyst. The components of the obtained cobalt-based refined Fischer-Tropsch wax are carbon distribution number in C 20 -C 100 The alkane, based on the total weight of the cobalt-based refined Fischer-Tropsch wax, has a normal alkane content of 98.9% by weight, wherein the cobalt-based refined Fischer-Tropsch wax C 10 -C 60 The normal alkane content is 24% by weight, C 61 -C 80 The normal alkane content is 32.5% by weight, C 81The above normal alkanes account for 42.4% by weight. The distillation range of the cobalt-based refined Fischer-Tropsch wax is 480-650°C, the wax content in the distillation range of 500-650°C accounts for 90% of the total weight of the cobalt-based refined Fischer-Tropsch wax, and the wax content in the distillation range of 550-650°C accounts for 85% of the total weight of the cobalt-based refined Fischer-Tropsch wax. The drop melting point of the cobalt-based refined Fischer-Tropsch wax is 114.5°C, and the aromatic content is 35ppm by weight.

[0165] The preparation method of cobalt-based hydrogenated Fischer-Tropsch wax is as follows: No. 120 cobalt-based Fischer-Tropsch wax is heated at 350°C, 7MPa, hydrogen-to-oil ratio of 600, and a feed space velocity of 1.2h -1 The cobalt-based hydrogenated Fischer-Tropsch wax was obtained by reacting with a cracking and isomerization composite catalyst (the weight ratio of 0.1% Pt / SAPO-11 and FC-32 catalyst was 1.5:1) under the reaction conditions. The properties of the cobalt-based hydrogenated Fischer-Tropsch wax are shown in Table 1.

[0166] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0167] Comparative Example 1

[0168] The coating wax was prepared according to the method of Example 1, except that no cobalt-based hydrogenated Fischer-Tropsch wax was added.

[0169] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0170] Comparative Example 2

[0171] The coating wax was prepared according to the method of Example 1, except that no cobalt-based refined Fischer-Tropsch wax was added.

[0172] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0173] Comparative Example 3

[0174] The coating wax was prepared according to the method of Example 1, except that no polyethylene wax was added.

[0175] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0176] Comparative Example 4

[0177] PE wax is prepared according to the raw materials and preparation method of application CN103305584A.

[0178] The PE wax was subjected to a performance test, and the test results are shown in Table 2.

[0179] Comparative Example 5

[0180] Traditional polyethylene wax. Polyethylene wax (purchased from Nanjing Tianshi, brand PEW-0300, average molecular weight 15000 g / mol) was tested for performance, and the test results are shown in Table 2.

[0181] Comparative Example 6

[0182] The coating wax was prepared according to the method of Example 1, except that when preparing the cobalt-based hydrogenated Fischer-Tropsch wax, all hydrocracking catalysts (i.e., FC-32 catalysts) were used, and no hydroisomerization catalyst (i.e., SLD-821 catalyst) was added.

[0183] The coating wax was subjected to a performance test, and the test results are shown in Table 2.

[0184] Table 1

[0185] Example 1 2 3 4 5 6 Average molecular weight (g / mol) 1200 1300 2000 1600 2500 2000 Drop melting point(℃) 70 80 100 90 90 80 Carbon number distribution <![CDATA[C 10 -C 80 ]]> <![CDATA[C 20 -C 90 ]]> <![CDATA[C 20 -C 120 ]]> <![CDATA[C 20 -C 100 ]]> <![CDATA[C 20 -C 90 ]]> <![CDATA[C 10 -C 90 ]]> Oil content (wt%) 0.5 0.4 0.2 0.2 0.3 0.4 Needle penetration (0.1mm) 12 8 7 8 7 10 Shrinkage rate (%) 0.8 0.6 0.5 0.5 0.6 0.7 100℃ Kinematic viscosity (mm / s) 11 14 12 18 19 16

[0186] Table 2

[0187]

[0188] It can be seen from the results in Table 2 that the embodiments of the coating wax of the present invention have higher gloss, higher hardness, higher impact resistance and adhesion than the comparative examples, and lower viscosity, ash content, oil content and shrinkage. The coating using the coating wax of the present invention has better temperature resistance and wear resistance, and is suitable for preparing both internal lubricants and external lubricants for precision instruments.

[0189] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A wax composition for coating, characterized in that: The wax composition comprises: cobalt-based refined Fischer-Tropsch wax, cobalt-based hydrogenated Fischer-Tropsch wax, polymer wax, microcrystalline wax, and stearic acid metal salt; Wherein, the cobalt-based refined Fischer-Tropsch wax refers to the Fischer-Tropsch wax that is hydrorefined using cobalt-based Fischer-Tropsch wax as raw material; The cobalt-based hydrogenated Fischer-Tropsch wax is a mixture of cobalt-based hydroisomerization Fischer-Tropsch wax and cobalt-based hydrocracking Fischer-Tropsch wax; the cobalt-based hydrogenated Fischer-Tropsch wax is prepared by the following method: cobalt-based Fischer-Tropsch wax is reacted in the presence of a hydrocracking and hydroisomerization composite catalyst to obtain the cobalt-based hydrogenated Fischer-Tropsch wax, the hydrocracking and hydroisomerization composite catalyst refers to a mixed catalyst of a hydroisomerization catalyst and a hydrocracking catalyst, and the weight ratio of the hydroisomerization catalyst to the hydrocracking catalyst is 0.2-3:1; Wherein, based on the total weight of the wax composition, the amount of the cobalt-based refined Fischer-Tropsch wax is 40-60% by weight, the amount of the cobalt-based hydrogenated Fischer-Tropsch wax is 10-20% by weight, the amount of the polymer wax is 6-25% by weight, the amount of the microcrystalline wax is 6-15% by weight, and the amount of the metal stearate is 3-20% by weight; The polymer wax is polyethylene wax; The wax composition also includes an additive and a dispersant.

2. The wax composition according to claim 1, wherein The average molecular weight of the high molecular weight polymer wax is 10000-25000 g / mol.

3. The wax composition according to claim 1 or 2, wherein The microcrystalline wax is at least one of No. 70 microcrystalline wax and No. 80 microcrystalline wax.

4. The wax composition according to claim 1 or 2, wherein The metal stearate is at least one of zinc stearate and calcium stearate.

5. The wax composition according to claim 1 or 2, wherein The cobalt-based refined Fischer-Tropsch wax has a drop melting point of 90-115°C and a carbon number distribution of C 10 -C 140 , the aromatic content is 30-100ppm by mass.

6. The wax composition according to claim 1 or 2, wherein Based on the total weight of the cobalt-based refined Fischer-Tropsch wax, the n-alkane content of the cobalt-based refined Fischer-Tropsch wax is above 95 wt %, wherein, based on the total weight of the cobalt-based refined Fischer-Tropsch wax, C 10 -C 60 The content of normal alkanes is 24-37% by weight, C 61 -C 80 The content of normal alkanes is 32.5-41.5% by weight, C 81 The content of the above normal alkanes is 25-42.4% by weight.

7. The wax composition according to claim 1 or 2, wherein The distillation range of the cobalt-based refined Fischer-Tropsch wax is 400-650° C., wherein the wax with a distillation range of 550-650° C. accounts for more than 45% by weight of the total weight of the cobalt-based refined Fischer-Tropsch wax.

8. The wax composition according to claim 1 or 2, wherein The cobalt-based hydrogenated Fischer-Tropsch wax has a drop melting point of 70-100° C., a kinematic viscosity of 11-30 mm / s at 100° C., and a carbon number distribution of C 10 -C 120 , 0.1mm needle penetration is 7-30, and the oil content is 0.01-5% by weight.

9. The wax composition according to claim 1 or 2, wherein The carbon number distribution of the cobalt-based hydrogenated Fischer-Tropsch wax is C 25 -C 120 .

10. The wax composition according to claim 1, wherein The auxiliary agent is selected from at least one of beeswax, PE oligomer, pentaerythritol stearate, ethylene bis stearic acid amide, emulsifier and rust inhibitor.

11. The wax composition according to claim 10, wherein Based on the total weight of the wax composition, the amount of the beeswax is 0.2-5% by weight, the amount of the PE oligomer is 1-10% by weight, the amount of the pentaerythritol stearate is 3-15% by weight, the amount of the ethylene bisstearamide is 2-20% by weight, the amount of the emulsifier is 1-5% by weight, and the amount of the rust inhibitor is 0.5-5% by weight.

12. The wax composition according to claim 10 or 11, wherein The average molecular weight of the PE oligomer is 7000-9000 g / mol.

13. The wax composition according to claim 10 or 11, wherein The mass ratio of the high molecular weight polymer wax to the PE oligomer is 0.2-2:

1.

14. The wax composition according to claim 10 or 11, wherein The rust inhibitor is at least one of triethanolamine, benzotriazole and pentaerythritol monooleate.

15. The wax composition according to claim 1 or 2, wherein Based on the total weight of the wax composition, the amount of the dispersant is 0.1-2% by weight.

16. A method for preparing coating wax using the wax composition according to any one of claims 1 to 15, characterized in that: The following steps are involved: (1) performing a first mixing and melting of cobalt-based refined Fischer-Tropsch wax and cobalt-based hydrogenated Fischer-Tropsch wax to obtain liquid Fischer-Tropsch wax; (2) performing a second mixing and melting of the liquid Fischer-Tropsch wax, a metal stearate and a dispersant to obtain a metal stearate Fischer-Tropsch wax mixture; (3) performing a third mixing and melting of the metal stearate Fischer-Tropsch wax mixture, the polymer wax and the microcrystalline wax to obtain a liquid mixed wax; (4) melting and mixing the liquid mixed wax and keeping it warm to obtain a liquid Fischer-Tropsch modified wax; (5) granulating and screening the liquid Fischer-Tropsch modified wax to obtain coating wax; Wherein, the auxiliary agent is added in step (3) and step (4) respectively or the auxiliary agent is added only in step (4).

17. The method for preparing a coating wax according to claim 16, wherein: In step (1), the temperature of the first mixed melting is 120-180° C., and the stirring speed of the first mixed melting is 10-50 r / min.

18. The method for preparing a coating wax according to claim 16 or 17, wherein: In step (2), the second mixing and melting temperature is 140-180° C., and the stirring speed is 10-50 r / min.

19. The method for preparing a coating wax according to claim 16 or 17, wherein: In step (3), the temperature of the third mixed melting is 140-180° C., and the stirring speed of the third mixed melting is 10-50 r / min.

20. The method for preparing a coating wax according to claim 16 or 17, wherein: In step (4), the melting temperature is 120-140°C, the insulation temperature is 150-175°C, the stirring speed during insulation is 10-50 r / min, and the insulation time is 1-6 h.

21. A coating wax obtained by the method according to any one of claims 16 to 20.

22. The coating wax according to claim 21, wherein The coating wax has a viscosity of less than 20 mm / s at 100° C., an ash content of less than 0.05% by weight, an oil content of less than 1.3% by weight, and a shrinkage rate of less than 1%.

23. The coating wax according to claim 21 or 22, wherein: The coating wax has an oil content of 0.6-1.2% by weight, a shrinkage rate of 0.1-0.8%, and an ash content of 0.002-0.005% by weight.

24. A coating, characterized in that: The coating contains the coating wax according to any one of claims 21 to 23.

25. Use of the coating wax according to any one of claims 21 to 23 or the coating according to claim 24 in precision instrument coatings.

Citation Information

Patent Citations

  • Method for splitting optically pure 2-octyl alcohol by adopting enzyme catalysis

    CN103305584A

  • PE (polyethylene) wax for hot-melt road marking coating and preparation method of PE wax

    CN110305584A

  • Antirust wax

    CN102618044A